ANALISIS EFEKTIFITAS-BIAYA ANTARA KOMBINASI SALBUTAMOL-IPRATROPIUM DENGAN SALBUTAMOL PADA SERANGAN ASMA - Amelia Lorensia; Ferdias Kurnia Bahari (Jurnal Insan Farmasi Indonesia, 2020)
Treatment of asthma exacerbation is necessary to get attention to get effective and efficient treatment. The first line of treatment for asthma exacerbation is nebulation salbutamol, but some asthma treatments require additional combinations of ipratropium. know the cost-effectiveness with the use of a combination of salbutamol and ipratropium bromide with salbutamol alone to improve asthma symptoms and length of treatment in patients with asthma attacks. The study design was retrospective from medical record data of asthma patients in a hospital in Surabaya in the period from January-October 2017. Dependent variables were cost and clinical outcome (duration of treatment and loss of breathless symptoms). Data analysis used was ACER calculation and different test. The subjects were 64 people, consisting of 23 people in group A (salbutamol-ipratropium) and 41 people in group B (salbutamol). Group A was more cost-effective in length of treatment and trade-off in reducing asthma symptoms than in group B. There was no significant difference between costs (p(0.816)> 0.05), length of treatment (p=0.386)> 0.05)) and improvement of asthma symptoms (p (0.676)> 0.05). Therefore, further research was needed on the level o f other asthma attacks and other cost/outcome components.